2002
DOI: 10.1084/jem.20011714
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Stimulation of the Cholinergic Antiinflammatory Pathway

Abstract: Efferent activity in the vagus nerve can prevent endotoxin-induced shock by attenuating tumor necrosis factor (TNF) synthesis. Termed the “cholinergic antiinflammatory pathway,” inhibition of TNF synthesis is dependent on nicotinic α-bungarotoxin-sensitive acetylcholine receptors on macrophages. Vagus nerve firing is also stimulated by CNI-1493, a tetravalent guanylhydrazone molecule that inhibits systemic inflammation. Here, we studied the effects of pharmacological and electrical stimulation of the intact va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
337
0
14

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 483 publications
(363 citation statements)
references
References 30 publications
9
337
0
14
Order By: Relevance
“…CVC can be improved via biofeedback (e.g., Nolan et al, 2005), leading to a reduction of depressive symptoms (Siepmann, Aykac, Unterdorfer, Petrowski, & Mueck-Weymann, 2008). CVC can also be enhanced by pharmacological and surgical means (Bernik et al, 2002; Singh, Kandala, & Camm, 2014). Interestingly, Tsai, Kuo, Lee, and Yang (2015) showed that slow-paced breathing (at a frequency of 0.1 Hz) can lead to increases in CVC as well, which improved sleep quality among individuals with insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…CVC can be improved via biofeedback (e.g., Nolan et al, 2005), leading to a reduction of depressive symptoms (Siepmann, Aykac, Unterdorfer, Petrowski, & Mueck-Weymann, 2008). CVC can also be enhanced by pharmacological and surgical means (Bernik et al, 2002; Singh, Kandala, & Camm, 2014). Interestingly, Tsai, Kuo, Lee, and Yang (2015) showed that slow-paced breathing (at a frequency of 0.1 Hz) can lead to increases in CVC as well, which improved sleep quality among individuals with insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…Injections. Rats were anesthetized and placed in a stereotaxic head frame (Stoelting) as described (6). The incisor bar was adjusted until the plane defined by the lambda and bregma was parallel to the base plate.…”
Section: Methodsmentioning
confidence: 99%
“…Activation of this anti-inflammatory pathway can be achieved by the following: 1) direct stimulation of the vagus nerve [16,17] , 2) the use of nicotine or nicotinic agonists (GTS-21, CAP55) to activate the α7nAChR [18][19][20] , and 3) the use of cholinesterase inhibitors (physostigmine, galantamine) [21][22][23] .…”
Section: Discussionmentioning
confidence: 99%